Exosomes in pathogenesis, diagnosis, and therapy of ischemic stroke - Jin, Meiqi; Zhang, Shuxia; Wang, Mengchen; Li, Qiaoyu; Ren, Jiahui; Luo, Yun; Sun, Xiaobo (Frontiers in Bioengineering and Biotechnology, 2022)
Ischemic stroke is one of the major contributors to death and disability worldwide. Thus, there is an urgent need to develop early brain tissue perfusion therapies following acute stroke and to enhance functional recovery in stroke survivors. The morbidity, therapy, and recovery processes are highly orchestrated interactions involving the brain with other tissues. Exosomes are natural and ideal mediators of intercellular information transfer and are recognized as biomarkers for disease diagnoses and prognosis. Changes in exosome content expression throughout the physiological process. Accumulating evidence demonstrates the use of exosomes in exploring unknown cellular and molecular mechanisms of intercellular communication and organ homeostasis and indicates their potential role in ischemic stroke. Inspired by the unique properties of exosomes, this review focuses on the communication, diagnosis, and therapeutic role of various derived exosomes, and their development and challenges for the treatment of cerebral ischemic stroke.